Corrosion in Natural Waters 1990
DOI: 10.1520/stp26099s
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Corrosivity Around the World: Results from Three Years of Testing

Abstract: A world-wide test program was undertaken by Task Group G 1.09.02.03 to assess the relative corrosivity of seawater at 14 test sites. Aluminum alloy A95086, copper-nickel alloy C70600, and carbon steel alloy KOI501 specimens were prepared at one location, shipped to the various sites, and returned to the original site for final evaluations. Results obtained through three years of testing indicate that average corrosion behavior was generally within limits of previously published results. Individual site charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For carbon steel exposed in natural seawater and in the presence of a fouling community, Griffin et al (1989) calculated Influence of macrofouling on carbon steel corrosion 197 0.085 mmpy after 3 years' immersion, and Palraj and Venkatachari (2006) described a rate of 0.152 mmpy after 1 year. Kirk and Pikull (1990) reported values between 0.075 and 0.200 mmpy for carbon steel exposed in seawater for a minimum of 6 months. These authors found average values of 0.168 mmpy over 6 months and 0.172 mmpy in 1 year, decreasing to 0.117 mmpy at the end of 3 years, emphasising that there was no temporal tendency of rate increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For carbon steel exposed in natural seawater and in the presence of a fouling community, Griffin et al (1989) calculated Influence of macrofouling on carbon steel corrosion 197 0.085 mmpy after 3 years' immersion, and Palraj and Venkatachari (2006) described a rate of 0.152 mmpy after 1 year. Kirk and Pikull (1990) reported values between 0.075 and 0.200 mmpy for carbon steel exposed in seawater for a minimum of 6 months. These authors found average values of 0.168 mmpy over 6 months and 0.172 mmpy in 1 year, decreasing to 0.117 mmpy at the end of 3 years, emphasising that there was no temporal tendency of rate increases.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to interpret the uniform corrosion rates considering the aspect of oxygen concentration cells on the panel surfaces. Kirk and Pikull (1990) and Gentil (1996) suggested that the uniform corrosion rate on carbon steel is directly associated with oxygen concentration: the rate increases in the presence of oxygen and decreases in minor concentrations. The present control treatment showed the highest uniform corrosion rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question for shallow waters is how to test for corrosion in an unexploited site. There have been many experiments done but none in the literature takes a detailed approach in profiling corrosion loss with depth in the past decade from the literature [26,27]. This will require a new design to accommodate the experiment to profile the corrosion rate and loss with depth and is explained below.…”
Section: Field Experiments Design and Deploymentmentioning
confidence: 99%
“…The seawater salinity in China seas is 1.5 times to 2 times higher than Baltic Sea in North Europe. Researches have proved that salinity around 3% is most corrosive [46], so more corrosion precautions should be used in China compared with North European countries. Usually titanium heat exchanger is used, which can be 2 to 3 times more expensive than heat exchangers made from other metallic materials [47].…”
Section: Heat Source: Spatial Seawater Sub-modelmentioning
confidence: 99%